Kegagalan Pelaksanaan Asesmen Autentik pada Pelajaran Pendidikan Agama Islam Di Sekolah Dasar Dan Menengah - Agung Prihantoro (Universitas Cokroaminoto Yogyakarta, 2021)
The article aimed to (1) describe how failure of the application of authentic assessment of Islamic education in Indonesia’s schools and madrasa was, (2) explain why the failure happened, and (3) explain what the failure implied. Using the systematic literature review, the article investigated 27 researches on authentic assessment practices. The conclusions are that (1) the failure were proved in very few features of authentic assessment at the practices, because (2) the teachers of Islamic education did not understand authentic assessment and in turn because campaign and training of authentic assessment were a minimum. (3) The failure implied in untrained studenrs to apply their acquired knowledge, higher order thinking skills and attitude in real life, identify and solve Muslim’s complex problems, collaborate and construct knowledge.